A systematic literature review on the use of platelet transfusions in patients with thrombocytopenia. Issue 1 (1st January 2019) - Newland, Adrian; Bentley, Roy; Jakubowska, Anna; Liebman, Howard; Lorens, Joanna; Peck-Radosavljevic, Markus; Taieb, Vanessa; Takami, Akiyoshi; Tateishi, Ryosuke; Younossi, Zobair M.
ABSTRACT: Objective: Investigate globally, current treatment patterns, benefit-risk assessments, humanistic, societal and economic burden of platelet transfusion (PT). Methods: Publications from 1998 to June 27, 2018 were identified, based on databases searches including MEDLINE®; Embase and Cochrane Database of Systematic Reviews. Data from studies meeting pre-specified criteria were extracted and validated by independent reviewers. Data were obtained for efficacy and safety from randomized controlled trials (RCTs); data for epidemiology, treatment patterns, effectiveness, safety, humanistic and societal burden from real-world evidence (RWE) studies; and economic data from both. Results: A total of 3425 abstracts, 194 publications (190 studies) were included. PT use varied widely, from 0%–100% of TCP patients; 1.7%–24.5% in large studies (>1000 patients). Most were used prophylactically rather than therapeutically. 5 of 43 RCTs compared prophylactic PT with no intervention, with mixed results. In RWE studies PT generally increased platelet count (PC). This increase varied by patient characteristics and hence did not always translate into a clinically significant reduction in bleeding risk. Safety concerns included infection risk, alloimmunization and refractoriness with associated cost burden. Discussion: In RCTs and RWE studies there was significant heterogeneity in study design and outcome measures. In RWE studies, patients receiving PT may have been at higher risk than those not receiving PT creating potential bias. There were limited data on humanistic and societal burden. Conclusion: Although PTs are used widely for increasing PC in TCP, it is important to understand the limitations of PTs, and to explore the use of alternative treatment options where available.